2005
DOI: 10.1007/s00442-005-0030-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal and embryo characteristics on post-fertilization provisioning in fishes of the genus Gambusia

Abstract: Maternal provisioning of embryos in Gambusia (Poeciliidae) entails both production of large, yolky eggs and mother-to-embryo transfer of nutrients, the latter of which is readily quantified using injection of radiolabeled nutrients. We assayed patterns of nutrient transfer in broods of 26 Gambusia geiseri and 23 Gambusia affinis females, using injection of tritiated leucine. We examined maternal and embryo characteristics affecting the instantaneous rate of transfer and characterized the pattern of transfer to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 66 publications
4
63
0
Order By: Relevance
“…The latter allows the fertilization and development of several broods simultaneously (MarshMatthews 2011; Pires et al 2011). The maternal transfer of nutrients such as amino acids has previously been reported for mosquitofish (Marsh-Matthews et al 2005), thus our findings of maternal copper transfer extends this finding to micronutrients, and to the least killifish-a species with a different provisioning mode. Copper is a component of various proteins and plays a role in many biochemical and physiological functions (Handy et al 2002;Kamunde and Wood 2004).…”
Section: Discussionsupporting
confidence: 85%
“…The latter allows the fertilization and development of several broods simultaneously (MarshMatthews 2011; Pires et al 2011). The maternal transfer of nutrients such as amino acids has previously been reported for mosquitofish (Marsh-Matthews et al 2005), thus our findings of maternal copper transfer extends this finding to micronutrients, and to the least killifish-a species with a different provisioning mode. Copper is a component of various proteins and plays a role in many biochemical and physiological functions (Handy et al 2002;Kamunde and Wood 2004).…”
Section: Discussionsupporting
confidence: 85%
“…Nutrient transfer was quantified by measuring radioactivity present in individual embryos. Marsh-Matthews et al (2005, for poeciliids) and Swain and Jones (1997, for a viviparous lizard) demonstrated that radiolabeled leucine is incorporated into the proteins of developing embryos within hours of injection of the mother. All embryo assays were done in the same scintillation run (with no correction necessary for counting efficiency), so radioactivity is expressed as counts per minute (cpm).…”
Section: Radio-tracer Assay Of Matrotrophymentioning
confidence: 98%
“…Lecithotrophic means that there is no placenta-like connection between the mother and young (Reznick and Yang, 1993), such that yolk stored in the egg is assumed to be the only source of embryo nutrition. Recent work within the Poeciliidae has indicated, however, that some mother-to-embryo nutrient transfer may occur in species thought to be lecithotrophic (Marsh-Matthews et al, 2005;Marsh-Matthews et al, 2011). To our knowledge, no attempt has been made to quantify any post-fertilization provisioning in P. reticulata, and it is not known to what degree there is a limited transfer of oxygen or small molecules.…”
Section: Experimental Animalsmentioning
confidence: 99%